HIV-1 Tat and Viral Latency: What We Can Learn from Naturally Occurring Sequence Variations - Kamori, Doreen; Ueno, Takamasa (Frontiers in microbiology, 2017)
Despite the effective use of antiretroviral therapy, the remainder of a latently HIV-1-infected reservoir mainly in the resting memory CD4 T lymphocyte subset has provided a great setback toward viral eradication. While host transcriptional silencing machinery is thought to play a dominant role in HIV-1 latency, HIV-1 protein such as Tat, may affect both the establishment and the reversal of latency. Indeed, mutational studies have demonstrated that insufficient Tat transactivation activity can result in impaired transcription of viral genes and the establishment of latency in cell culture experiments. Because Tat protein is one of highly variable proteins within HIV-1 proteome, it is conceivable that naturally occurring Tat mutations may differentially modulate Tat functions, thereby influencing the establishment and/or the reversal of viral latency In this mini review, we summarize the recent findings of Tat naturally occurring polymorphisms associating with host immune responses and we highlight the implication of Tat sequence variations in relation to HIV latency.